Transition through design: enabling innovation via empowered ecosystems. Issue 5 (3rd May 2020) - Komatsu Cipriani, Tamami; Kaletka, Christoph; Pelka, Bastian
ABSTRACT: The problems society faces today are increasingly complex and rooted in likewise complex socio-technical systems. Unfortunately, the structures meant to face these challenges are not suitably equipped. There is a mismatch between the need and the capacity to respond. Design methods and approaches are now being employed to help capacitate cities and communities and structure social innovations around larger transition visions. As social innovations are highly context-dependent, the distinctive characteristics of the local context become important to the success or failure of such initiatives. In the paper, the authors explore this topic through the study of two cases in which top-down visions, negotiated at the niche-level, gave way to the structuration of an empowered ecosystem of actors, serving as a platform for iterative, social change. The cases are analyzed through an 'Onion model' in which four contexts are explored: roles, functions, structures and norms.